High Performance Non-Enzymatic Electrochemical Lactate Sensor Based on ZnAl Layered Double Hydroxide Nanosheets Supported Gold Nanoparticles. Issue 5 (27th May 2021) - Djebbi, Mohamed Amine; Boubakri, Saber; Braiek, Mohamed; Jaffrezic-Renault, Nicole; Namour, Philippe; Ben Haj Amara, Abdesslem
Abstract : Lactate monitoring in body being of utmost importance in clinical diagnostics. It is a vital biomarker in the anaerobic metabolic pathway of humans, its elevation may lead to respiratory or hepatic failure and many more diseases and physiological fatigue. In this research, we propose a low-cost and high performance non-enzymatic electrochemical sensor aimed at the detection of lactate. The sensor was fabricated by assembling ZnAl layered double hydroxide (LDH) nanosheets along with gold nanoparticles (AuNPs) onto boron doped diamond electrodes (BDD). The as-prepared materials were characterized by X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FT-IR), UV–visible spectrophotometry (UV–vis), transmission (TEM) and scanning (SEM) electron microscopy, while the modified electrode was characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The electrochemical measurements for lactate binding were performed using square wave voltammetry (SWV), revealed high sensitivity of 13.9 μ A/ μ M/cm 2, broad detection range of 0.1–30 μ M and low detection limit up to 0.1 μ M. Besides, the proposed lactate sensor possessed excellent long-term stability, good reproducibility, repeatability and selectivity. The response currents of detection in biological samples were also close to the standard solutions. Therefore the developed sensor is promising to be used in clinical practice.